(untitled) (Economic studies journal, 2020)
This study aims to identify the extent of commitment of the Libyan commercial banks (Jomhouria sahara ,national commercial and wahda ) to the central bank of Libya circular number (3) 2005 regarding liberalizing the prices of banking services and the criteria for determining them and impact on the quality of banking services. To achieve this objective, questionnaire was designed and distributed to the study population, which consists of client and customers of that were previously mentioned. Four hundred validquestionnaires out of the distributed 298 copies were returned, analyzed using (SPSS). The study concludes that the banks under the study donot adhere to the central bank of Libya circular number (3) 2005, and there is also decrease in the dimensions of the quality of banking services, from the viewpoint of the clients of those banks under study. The study recommends that commercial banks should be adhere to the central bank of Libya circular no (3) 2005. Regarding liberalizing the prices of banking services and their controls, and attention be paid to improving the quality of banking services represented (tangibility, reliability, responsiveness, sympathy).